2014
DOI: 10.1016/j.evalprogplan.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Improving the oral health of residents with intellectual and developmental disabilities: An oral health strategy and pilot study

Abstract: This article presents an oral health (OH) strategy and pilot study focusing on individuals with intellectual and/or developmental disabilities (IDD) living in group homes. The strategy consists of four components: (1) planned action in the form of the behavioral contract and caregiver OH action planning; (2) capacity building through didactic and observation learning training; (3) environmental adaptations consisting of additional oral heath devices and strategies to create a calm atmosphere; and (4) reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…However, there was anecdotal evidence of some improvements. Other studies have highlighted the challenges in changing oral health behaviours for this subpopulation (Binkley, Johnson, Abadi, Thompson, Shamblen et al, 2014;Pradhan, Keuskamp & Brennan, 2015), and more intensive efforts would likely be required than were employed in this study. For the general population, systematic reviews of the evidence for oral health promotion effectiveness have not been definitive.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was anecdotal evidence of some improvements. Other studies have highlighted the challenges in changing oral health behaviours for this subpopulation (Binkley, Johnson, Abadi, Thompson, Shamblen et al, 2014;Pradhan, Keuskamp & Brennan, 2015), and more intensive efforts would likely be required than were employed in this study. For the general population, systematic reviews of the evidence for oral health promotion effectiveness have not been definitive.…”
Section: Discussionmentioning
confidence: 99%
“…() and Binkley et al . (). While behavioural issues among people with disabilities remain a challenging problem for carers and dental professionals, disability organisations and researchers could explore the reasons for the high turnover and mobility of carers.…”
Section: Discussionmentioning
confidence: 97%
“…() in Ireland and Binkley et al . () in the United States, who found that their training had varied impacts on carers. In this pilot study, training methods from these two studies have been combined for a more effective intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations